SAFETY AND EFFICACY OF MYCOPHENOLATE MOFETIL TREATMENT FOR REFRACTORY CROHN'S DISEASE. (26th January 2023) - Rosenfeld, Sam; Clark-Snustad, Kindra; Kamp, Kendra; Barahimi, Mitra; Harper, Jason; Jacobs, Jeffrey; Lee, Scott D
Abstract: BACKGROUND: Medically refractory Crohn's disease is a significant challenge with poor remission rates and limited medication options. Mycophenolate mofetil (MMF), a small molecule immune suppressant, has mixed data to support its use in Crohn's disease and has not been studied in refractory disease or biologic experienced patients. AIMS: We aimed to evaluate the safety and efficacy of off-label clinical MMF treatment for refractory Crohn's disease as monotherapy or in combination with a biologic. METHODS: We retrospectively assessed adverse events (AEs), clinical response (Harvey-Bradshaw Index, HBI), endoscopic response (Simple Endoscopic Score in Crohn's Disease, SES-CD), and physician's subjective assessment (scale of 0-3) over 52 weeks at a single medical system including an academic medical center and county hospital. RESULTS: 61 patients received MMF as monotherapy (n=41) or in combination with a biologic (n=20) between 2008 and 2021 at a dose ranging from 500 – 2000 mg BID. Median age was 39 years (range 19-69) and median disease duration was 11 years (range 2-54). All patients had failed one or more TNF-alpha antagonist; the median number of failed biologics was 4. Median duration of therapy was 27 weeks. Of patients with requisite data, 14/27 (52%) achieved clinical response (HBI decreased by ≥3) after mean 24.2 weeks (SD 20.4). 6/27 (22%) achieved clinical remission (HBI ≤4). Endoscopic response (SES-CD reduction ≥50%) occurred in 7/26 patients (27%) after mean 43.5 weeks (SD 29.5). Endoscopic remission (SES-CD ≤3) occurred in 4/26 patients (15%) and endoscopic healing (SES-CD =0) in 2/26 patients (8%). Per physician's subjective assessment, 17/51 patients (33%) achieved clinical response (score improved by ≥1), 16/51 (31%) achieved clinical remission (score of 0 or 1), 10/34 patients (29%) achieved endoscopic response and 9/34 patients (26%) achieved endoscopic remission. Table 1 shows clinical and endoscopic response separated by monotherapy or in combination with a biologic. AEs were reported in 27/61 patients (44%); 16 on monotherapy and 11 on combination. Most common AEs were mild infection, nausea/vomiting, abdominal pain, and diarrhea. Nausea/vomiting and diarrhea led to early discontinuation for several patients. Serious adverse events occurred in 2/61 patients (pneumonia requiring hospitalization and SVT) both on monotherapy. CONCLUSIONS: MMF appears well-tolerated and results in clinical and endoscopic benefit for some patients with refractory Crohn's disease. This study is limited by uncontrolled, retrospective design and small numbers that were eligible for analysis. The results support additional prospective testing of MMF either as monotherapy or in combination with a biologic for patients with refractory Crohn's disease.